The role of normothermic machine perfusion (NMP) in the preservation of ex-vivo liver before transplantation: A review - Shen, Chuanyan; Cheng, Hongwei; Zong, Tingting; Zhu, Hongli (Frontiers in Bioengineering and Biotechnology, 2023)
The discrepancy between the number of patients awaiting liver transplantation and the number of available donors has become a key issue in the transplant setting. There is a limited access to liver transplantation, as a result, it is increasingly dependent on the use of extended criteria donors (ECD) to increase the organ donor pool and address rising demand. However, there are still many unknown risks associated with the use of ECD, among which preservation before liver transplantation is important in determining whether patients would experience complications and survival after liver transplantation. In contrast to traditional static cold preservation of donor livers, normothermic machine perfusion (NMP) may reduce preservation injury, improve graft viability, and potentially allows ex vivo assessment of graft viability before transplantation. Data seem to suggest that NMP can enhance the preservation of liver transplantation to some extent and improve the early outcome after transplantation. In this review, we provide an overview of NMP and its application in ex vivo liver preservation and pre-transplantation, summarized the data from current clinical trials of normothermic liver perfusion.